Introduction: Politeness and impoliteness in computer-mediated communication - Locher, Miriam A. (Journal of politeness research : language, behaviour, culture, 2010)
This special issue of the journal deals with how interactants negotiate the relational aspect of language use in computer-mediated contexts; a subject matter which has received scant attention to date. It offers a range of articles on impoliteness and politeness strategies in various computer-mediated communication settings, using data from different language backgrounds and practices. Adapted from the source document